Effects of boron application on the germination, growth and nutrient uptake by Amaranthus gangeticus and Amaranthus lividus (SAARC Journal of Agriculture, 2023)
Boron (B) is required for a variety of physiological and biochemical activities that contribute to crop quality improvement. As a result, a pot experiment was carried out to see how B affected the germination, growth, and nutritional intake of two common vegetables, red Amaranthus (Amaranthusus gangeticus) and stem Amaranthus (Amaranthusus lividus). The trial included four levels of B (0, 1, 1.5, and 2 kg ha-1) and three replications in a completely randomized design. The results showed that the application of B had no effect on germination, shoot and root length of red Amaranthus seedlings but it did reduce stem Amaranthus germination to 40% at the maximum dosage of B (2 kg ha-1). With increasing B concentration, stem Amaranthus seedlings' shoot and root lengths decreased significantly (p≤0.05). After applying B at a rate of 1.5 kg ha-1, yield, dry weight, fresh weight, leaf number, height, and protein content of both vegetables increased significantly, although higher B concentrations (2 kg B ha-1) tended to decrease the same parameters. The addition of B enhanced the concentration and uptake of nutrients (N, P, K, Ca, Mg, and B) in both vegetables as compared to control. Phosphorus had the highest nutrient utilization efficiency, whereas calcium had an increased efficiency as B concentration increased. Application of 1.5 kg B ha-1 had the highest B use efficiency for both vegetables. According to the findings, using B at a rate of 1.5 kg B ha-1 could help increase red Amaranthus and stem Amaranthus production.SAARC J. Agric., 21(1): 67-78 (2023)